A STUDY ON IMPACT OF COVID-19 AND POTENTIAL OPPORTUNITIES FOR INDIA’S FOREIGN TRADE - Bhatia, Shubhra; Vaydande, Neeta; Adwani, Vinod (AU Hybrid International Conference 2024 on " Entrepreneurship & Sustainability in the Digital Era" under the theme of "People Centric Knowledge in Intelligence World", 2021)
Indian’s foreign trade has been a ride on roller coaster since few years. However the situation is now appalling than the previous framework with an immediate outburst of universally spread covid 19. It is not for the first time the global economy is witnessing economic slowdown. History reveals that the world has undergone many critical financial crunches in the past years. There were numerous epidemics that trapped many countries earlier too subsequently resulting into difficult socio-economic consequences. Economies have always been battling with such issues however revival hope was never been so fade that the entire world is experiencing today with the outbreak of Covid-19. Moreover the necessity of implementing lockdown in order to disconnect the chain of virus has made the situation worse for the world’s major economies in general and for India in specific. Since liberalisation the situations seemed to be improving due to major policy initiatives on the part of the government and various structural and fiscal reformations have brought our foreign trade to an improved position. However the trade balance of India has always witnessed negative except few years with increased exports and comparatively more increased imports. Despite of this no economy in the world has had GDP growth of 7% for a long period. But due to some decisions and new policy introduction like demonetisation and GST, India’s foreign trade has come to an unfavourable position and the gap between India’s exports and imports has been growing bigger and bigger. The situation is now growing worse than the previous scenario with an immediate outburst of universally spread covid 19. Therefore an attempt has been made to write the research paper with an objective to highlight impact of covid-19 and also to unfold and evaluate potential opportunities to India’s foreign trade because foreign trade is an instrumental part of economics and is considered as an engine of economic activity. India’s foreign trade position and policies may serve as the ‘ventilator’ that could be a crucial equipment in keeping the economy alive and on a course of recovery.